(untitled) (Biological Sciences - PJSIR, 2002)
Results of studies carried out on the combu stion of Lakhara lignite in Atmospheric Fluidized Bed Combustor (AFBC) are presented. Investigations cover some of the aspects of combustion including ash and environmental monitori ng. It has been concluded that AFBC of lignitic coals is safe if sulphur content of coal i s less than 4% as there is an optimum limit of addition of CaC0 as sorbent. It is important for the combu stor designer to keep in mind about the burnin g rates, burn-out times and temperature of char particles which may create some problem s during heating.